2011
DOI: 10.1007/s12032-011-9979-8
|View full text |Cite
|
Sign up to set email alerts
|

Phase I and pharmacokinetic study of trabectedin 3-hour infusion every three weeks in patients with advanced cancer and alteration of hepatic function

Abstract: Maximum tolerated dose (MTD), recommended dose (RD), and pharmacokinetics (PK) were evaluated for trabectedin 3-h every-3-weeks schedule in 33 cancer patients stratified according to liver dysfunction degree as per baseline alkaline phosphatase (AP). Stratification was as follows: stratum I [upper limit of normal (ULN) < AP ≤ 1.5 × ULN; n = 16], stratum II [1.5 × ULN < AP ≤ 2.5 × ULN; n = 12], and stratum III [AP >2.5 × ULN; n = 5] (bilirubin <2.5 × ULN for all 3 strata). In each stratum, patients were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…3d). Because the clearance of trabectedin correlated with clearance of midazolam, it is apparent that the clearance of trabectedin depends on the hepatic clearance by CYP3A4 which is a main metabolism enzyme for trabectedin [23]. It is reported that there is not ethnic difference over individual difference in pharmacokinetics of midazolam [24].…”
Section: Discussionmentioning
confidence: 99%
“…3d). Because the clearance of trabectedin correlated with clearance of midazolam, it is apparent that the clearance of trabectedin depends on the hepatic clearance by CYP3A4 which is a main metabolism enzyme for trabectedin [23]. It is reported that there is not ethnic difference over individual difference in pharmacokinetics of midazolam [24].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly enough, there was no difference in serum level of markers of liver function (bilirubin, transaminases, etc) according to different serum AP levels;39 this finding has been confirmed in a pharmacokinetic analysis in which no relation was evident between AP or transaminase levels with trabectedin pharmacokinetics 31. In conclusion, as far as the available data are concerned, trabectedin (at the dose of 1.3 mg/m 2 ) can be utilized in patients with mild hepatic dysfunction, who nevertheless should be closely monitored 39…”
Section: Trabectedin Pharmacokinetic Features and Phase I Studiesmentioning
confidence: 91%
“…Moreover, the distribution volume at steady state was generally reported to be large (up to 4,000 L) in the weekly administration as well as in the 3-weekly schedules 3239…”
Section: Trabectedin Pharmacokinetic Features and Phase I Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common side effects are fatigue, nausea, anorexia, vomiting, constipation, atelectasis, dyspnoea, neutropenia, haemorrhoids, and intestinal obstruction. There were no indications of renal toxicity in rats (or mice and dogs) [ 7 , 14 , 17 , 18 ]. There is also no cardiac toxicity and no ECG changes (considered as prolongation of QT/QTc interval) after treatment with trabectedin [ 17 ].…”
Section: Trabectedin As a Single Agentmentioning
confidence: 99%